Evaluation of an individual‐donation nucleic acid amplification testing algorithm for detecting hepatitis B virus infection in Chinese blood donors. Issue 9 (15th July 2015) - Gou, Hongna; Pan, Yang; Ge, Hongwei; Zheng, Yourong; Wu, Yaling; Zeng, Jinfeng; Yang, Zhongsi; Pan, Tong; Cun, Wei; Zhou, Guoping; Fang, Gen; Zhang, Jiahong; et al.
Abstract : BACKGROUND: This multicenter study was performed to evaluate the efficiency of a multiplex individual‐donation nucleic acid amplification technology (ID‐NAT) and discriminatory testing algorithm for detecting hepatitis B virus (HBV) infection in Chinese blood donors. STUDY DESIGN AND METHODS: A total of 1, 205, 796 hepatitis B surface antigen (HBsAg)‐nonreactive donations from 10 blood centers were tested by ID‐NAT using the Ultrio assay. Multiplex Ultrio‐reactive donations were tested in the discriminatory tests as well as in quantitative polymerase chain reaction (qPCR) and in supplemental electrochemiluminescence immunoassays for HBsAg, hepatitis B surface antibody (anti‐HBs), hepatitis B e antigen, and antibody to hepatitis B core antigen (anti‐HBc). Meanwhile, a control group of 4317 Ultrio‐nonreactive donations was tested for anti‐HBc and anti‐HBs. RESULTS: Of all donations, 2033 (0.17%) were reactive in the multiplex Ultrio assay. Among 1776 further tested samples, 548 (30.9%) were HBV discriminatory assay (dHBV)‐reactive, while 1214 (68.4%) were nonreactive. Of 472 Ultrio+ and dHBV+ samples 86.2% were qPCR positive compared to 15.0% in 1046 Ultrio+ and dHBV– samples. The proportion of anti‐HBc+ and anti‐HBs– (potentially infectious) donations was higher in 409 Ultrio+ and dHBV+ than in 1028 Ultrio+ and dHBV– samples (51.3% vs. 31.1%, p < 0.001). The yield rate of Ultrio+, dHBV+, and qPCR+ donations was estimated at 1 in 2500, but at 1 in 1100 when all supplemental tests were taken into account assuming that 44% of detected donations by Ultrio were false reactive. CONCLUSIONS: A quarter of HBsAg‐negative Ultrio+ and dHBV– donations in China are likely given by potentially infectious low‐viral‐load occult carriers. Although this has no implication for blood safety, the testing algorithm needs to be redesigned to more efficiently discriminate between true and false NAT reactivity.